Functional Transcriptomic Analysis of Centenarians' Offspring Reveals a Specific Genetic Footprint That May Explain That They Are Less Frail Than Age-Matched Noncentenarians' Offspring. Issue 10 (28th May 2022) - Inglés, Marta; Belenguer-Varea, Angel; Serna, Eva; Mas-Bargues, Cristina; Tarazona-Santabalbina, Francisco J; Borrás, Consuelo; Vina, Jose
Abstract: Centenarians exhibit extreme longevity and compression of morbidity and display a unique genetic signature. Centenarians' offspring seem to inherit centenarians' compression of morbidity, as measured by lower rates of age-related pathologies. We aimed to ascertain whether centenarians' offspring are less frail and whether they are endowed with a "centenarian genetic footprint" in a case–control study, matched 1:1 for gender, age ±5 years, and place of birth and residence. Cases must have a living parent aged 97 years or older, aged 65–80 years, community dwelling, not suffering from a terminal illness, or less than 6 months of life expectancy. Controls had to meet the same criteria as cases except for the age of death of their parents (not older than 89 years). Centenarians were individuals 97 years or older. Frailty phenotype was determined by Fried's criteria. We collected plasma and peripheral blood mononuclear cells from 63 centenarians, 88 centenarians' offspring, and 88 noncentenarians' offspring. miRNA expression and mRNA profiles were performed by the GeneChip miRNA 4.0 Array and GeneChip Clariom S Human Array, respectively. We found a lower incidence of frailty among centenarians' offspring when compared with their contemporaries' noncentenarians' offspring ( p < .01). Both miRNA and mRNA expression patterns in centenarians' offspring were more like those of centenarians than those of noncentenarians' offspring ( p < .01). In conclusion, centenarians' offspring are less frail than age-matched noncentenarians' offspring, and this may be explained by their unique genetic endowment.